THE INFLUENCE OF HYDROCHLORIC ACID (HCl) ACTIVATOR CONCENTRATION TO ADSORPTION CAPACITY OF CHARCOAL ACTIVE OF DURIAN’S PEEL (DURIO ZIBETHINUS) TO SUBSTANCE COLOUR OF METHANIL YELLOW - Sitti Chadijah; Supiati - (PROSIDING SEMINAR KIMIA, 2015)
Durian’s peel is a waste which usually burned, stacked or disintegrated and can make pollution to the environment. This condition motivates the researcher to produce the value-added product from the durian’s peel, such as activated carbon and as well as it can solve the environmental problems. This research aims to know the influence to use variation of concentration of activator HClwhice produces the optimum adsorption capacity from charcoal active of durian’s peel to the substance color of methanil yellow. Active carbon which is used in this research comes from durian’s peel which granular types with standard -100+40 mesh. Carbon is activated by physics in furnace with 400°C heat during 2 hours and is activated by chemistry with submerged of HCI 1M, 2M, 3M, 4M and 5M during 24 hours. The result of this research shows that optimum concentration in HCI 1M with adsorption capacity from charcoal active of durian’s peel is as large as 0,5350 mg/g. Whereas knowing the influence of activator is used tabulation method by statistically, where we can get FHitung 0,004 is smaller from FTabel 10,127. It explains that H0 is accepted to reject H1. Therefore, it can conclude that there is not significant influence to use variation of concentration of activator HCl to adsorption capacity of charcoal active from durian’s peel in substance methanil yellow.